Low vitamin D intake is associated with anemia in women of reproductive age in Vietnam - Smith, Ellen; Gonzalez-Casanova, Ines; Nguyen, Phuong Hong; Nguyen, Hieu; Pham, Hoa; Truong, Truong; Nguyen, Son; Martorell, Reynaldo; Ramakrishnan, Usha (Wiley, 2014)
We used baseline data from the PRECONCEPT study (a preconceptual micronutrient trial) to examine associations between vitamin D intake and anemia (hemoglobin < 12 g/dL) in 4961 Vietnamese women of reproductive age.Nutrient intake was estimated using a semi‐quantitative food frequency questionnaire and Vietnamese food composition tables. Linear and logistic regression models were used to assess factors associated with vitamin D intake and anemia, respectively.Mean hemoglobin concentration was 13.0 ± 1.4 g/dL and 19.6% were anemic. Median daily vitamin D intake was 0.2 µg (IQR: 0.4), below the recommended intake of 15 µg/day. Age, being a farmer, food insecurity, and body mass index were inversely associated with vitamin D intake (p<0.001), and socioeconomic status, total energy intake, and level of education were positively associated with vitamin D intake (p<0.001) in multiple linear regression analysis with vitamin D intake as the outcome. Vitamin D intake was significantly associated with the risk of anemia and, the association remained significant after adjusting for age and total energy intake (OR: 0.82, 95% CI: 0.72, 0.92).In conclusion, vitamin D intake was associated with better social status, and greater vitamin D intake may be protective of anemia.Supported by The Micronutrient Initiative and the Mathile Institute for the Advancement of Human Nutrition